2019
DOI: 10.1016/j.colcom.2018.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Inverse-Micelle Synthesis of Doxorubicin-Loaded Alginate/Chitosan Nanoparticles and In Vitro Assessment of Breast Cancer Cytotoxicity

Abstract: Naturally-derived polysaccharides, such as alginate and chitosan, can be assembled to form nanocarriers for the delivery of therapeutic agents. Here we exploit the electrostatic complexation of alginate/chitosan in a water-in-oil (w/o) emulsion process to produce doxorubicin (DOX)-loaded nanoparticles (~80 nm) with exceptional spherical morphology and uniformity. This robust synthetic route utilizes an aqueous phase dispersed in a cyclohexane/dodecylamine organic phase and is capable of encapsulating DOX in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 28 publications
2
14
0
Order By: Relevance
“…The amoxicillin encapsulation efficiency in Cs-Al NDs was calculated from a supernatant by triplicate, giving an efficiency of 74:98% ± 0:23. This result indicates that these nanodisks are a suitable material for a successful loading of amoxicillin and was consistent with the results reported in the literature of other chitosan/alginate nanoparticles [36,40,43]. The presence of the STPP crosslinking agent influences the encapsulation efficiency characteristic due to the formation of chitosan/alginate-TPP complex that produces an electrostatic interaction between carboxylic and amine functional groups of chitosan and amoxicillin, increasing the loading of amoxicillin in Cs-Al NDs [44].…”
Section: Encapsulation Efficacy Andsupporting
confidence: 90%
See 2 more Smart Citations
“…The amoxicillin encapsulation efficiency in Cs-Al NDs was calculated from a supernatant by triplicate, giving an efficiency of 74:98% ± 0:23. This result indicates that these nanodisks are a suitable material for a successful loading of amoxicillin and was consistent with the results reported in the literature of other chitosan/alginate nanoparticles [36,40,43]. The presence of the STPP crosslinking agent influences the encapsulation efficiency characteristic due to the formation of chitosan/alginate-TPP complex that produces an electrostatic interaction between carboxylic and amine functional groups of chitosan and amoxicillin, increasing the loading of amoxicillin in Cs-Al NDs [44].…”
Section: Encapsulation Efficacy Andsupporting
confidence: 90%
“…Accordingly, these results from the CellTiter 96® AQueous method are more reliable and the cytotoxicity pattern observed seems to be in agreement with other reports, in which higher concentration of nanoparticles is the main cause of inducing negative effects on the cell viability [58]. Among these reports, the use of alginate/chitosan and other types of nanocarriers against different cells lines was involved, and the results showed a similar trend in which a variation in the cell viability may be attributed to the selectivity with no discrimination toward the normal and cancerous cells [1,36,40,59].…”
Section: International Journal Of Polymer Sciencesupporting
confidence: 89%
See 1 more Smart Citation
“…However, due to the proliferation and metastasis of breast cancer cells (BCCs) remaining after chemotherapy, BC patients still face a relatively high recurrence rate and metastasis rate after being treated, which is the main death cause of them. 2,3 Therefore, it is still a great clinical challenge to deal with the recurrence and metastasis of BC, and it is of great clinical significance to find alternative therapies to replace traditional chemotherapy methods in solving the recurrence and metastasis caused by chemotherapy resistance. 4 A previous study reported that the disorder of histone lysine methylation intensified the invasiveness of BCCs.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo studies demonstrated that the formed complex nanoparticles (diameters below 200 nm) had superior sarcoma tumor inhibition rates at 83.17% and faint toxicity, compared with uncoated DOX nanoparticles and free DOX. Employing a water-in-oil emulsification technique, Rosch et al prepared DOX-loaded alginate/chitosan nanoparticles (~80 nm) [ 92 ]. It was shown that the nanoparticles were rapidly taken up by 4T1 murine breast cancer cells and produced high enough concentration to induce a therapeutic effect in vitro .…”
Section: Functionalization Strategies Of Alginate-based Platforms mentioning
confidence: 99%